Experimental Study of Air-Water Heat Exchanger as a Passive Coolant in Air Vents - Rafi Rahmat Ichsan; Remon Lapisa; Primawati Primawati; Budi Syahri (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Indonesia, a tropical climate country, has experienced a notable increase in temperatures during the dry season due to global warming, leading to decreased thermal comfort. This experimental study aims to investigate and analyze the performance of an air-water heat exchanger serving as a passive cooler in tropical ventilation systems. Before being introduced into the room, the hot outdoor air is passively cooled by colder water. Air, propelled by an inline duct fan at a constant speed of 9.6 meters per second, passes through a PVC hose integrated into a tube filled with water measuring 100 cm in diameter and 110 cm in height, which serves as the main heat exchanger. Measurement results indicate that the designed air-water heat exchanger provides a significant passive cooling effect, reducing air temperature by up to 6.83°C. By harnessing passive cooling, the cooling capacity achieved during the measurement period in the ventilation system ranges from 3.08 kJ to 7.67 kJ. Indonesia, yang memiliki iklim tropis, mengalami kenaikan suhu yang cukup besar selama musim kemarau akibat pemanasan global, sehingga mengurangi kenyamanan termal. Penelitian eksperimental ini bertujuan untuk menguji dan menganalisis kinerja alat penukar panas udara-air yang berfungsi sebagai pendingin pasif dalam sistem ventilasi di daerah tropis. Sebelum masuk ke dalam ruangan, udara panas dari luar didinginkan secara pasif oleh air yang lebih dingin. Udara yang didorong oleh kipas saluran udara dengan kecepatan tetap sebesar 9,6 meter per detik melewati selang PVC yang terhubung dengan tabung berisi air berdiameter 100 cm dan tinggi 110 cm, yang berperan sebagai penukar panas utama. Hasil pengukuran menunjukkan bahwa penukar panas udara-air yang dirancang memberikan efek pendinginan pasif yang signifikan, mengurangi suhu udara hingga 6,83 °C. Dengan memanfaatkan pendinginan pasif, kapasitas pendinginan yang dicapai selama periode pengukuran dalam sistem ventilasi berkisar antara 3,08 kJ hingga 7,67 kJ.